Folk-telling and Freire’s (1970) framework of banking versus dialogical methods of education – In search of innovation and social cohesion - Charamba, Tyanai (Midlands State University, 2014)
Freire (1972) established what he termed banking methods of education on one hand and dialogical methods of education on the other. For freire, banking methods of education should be discouraged whilst dialogical methods should be promoted in educational circles. Freire feels that the banking method of education should be discouraged since it kills a shared sense of education between the teacher and the learner. As such, it encourages learning by rote. That being the case, Freire feels that it is dialogical education that should be promoted in education circles since it promotes participatory education and in doing so, it curtails rote learning. This paper discusses how the art of folk telling discouraged banking methods of teaching the young and how it promoted dialogical education in Shona traditional societies. The paper also discusses how modern formal education promotes banking methods of teaching folktales at the expense of dialogical methods. Furthermore, the paper discusses the sort of innovation that can be improvised to restore the use of dialogical methods of education in the art of folk-telling in Zimbabwe. The researcher will use document analysis and in-depth personal interviews to gather data for this research endeavour.